2000
DOI: 10.1103/physreva.62.042303
|View full text |Cite
|
Sign up to set email alerts
|

Optically simulating a quantum associative memory

Abstract: This paper discusses the realization of a quantum associative memory using linear integrated optics. An associative memory produces a full pattern of bits when presented with only a partial pattern. Quantum computers have the potential to store large numbers of patterns and hence have the ability to far surpass any classical neural network realization of an associative memory. In this work two 3-qubit associative memories will be discussed using linear integrated optics. In addition, corrupted, invented and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Ventura and Martinez addressed the issue of associative memories and showed that Quantum Computer (QC) could effectively realize these devices [8,26]. Discussing the realization of quantum associative memory (QuAM), two 3-qubit associative memories have been incorporated and the corrupted, invented, and degenerate memories have been discussed [27]. The storage and recall mechanism of QuAM are fundamentally different from the traditional associative schemes such as Hopfield, bidirectional associative memory (BAM) etc.…”
Section: Recall Operation Of Quam Through Evolutionary Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventura and Martinez addressed the issue of associative memories and showed that Quantum Computer (QC) could effectively realize these devices [8,26]. Discussing the realization of quantum associative memory (QuAM), two 3-qubit associative memories have been incorporated and the corrupted, invented, and degenerate memories have been discussed [27]. The storage and recall mechanism of QuAM are fundamentally different from the traditional associative schemes such as Hopfield, bidirectional associative memory (BAM) etc.…”
Section: Recall Operation Of Quam Through Evolutionary Processesmentioning
confidence: 99%
“…Thus Bell's states do not provide a suitable choice as memory states for memory recall mechanism of QuAM. Let us examine the suitability of a MES as memory state |ψ 0 > for recalling the memory associated with a given partial pattern by the recall mechanism [27]:…”
Section: Recall Operation Of Quam Through Evolutionary Processesmentioning
confidence: 99%
“…Therefore, we examine algorithms which require few QND operations. One example is a Grover's search algorithm [3,5,6,25,26]. The primary function of Grover's search algorithm is to take some initial state ji͘ and transform it into some target state jt͘.…”
mentioning
confidence: 99%
“…The symmetric fiber coupler performs the discrete Fourier transform (DFT) in the subcircuits [5,6] and will be denoted F a where the subscript a denotes which subcircuit. The matrix elements of the DFT are given by where j, k have values 0, 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation